A qualificadora 'no melhor conhecimento' em contratos de compra e venda de participação societária - Cunha, Juliana Bonanza Teixeira da (2016)
The transactions involving the purchase and sale of equity in Brazil follow a model imported from international law. Among all imported institutes, there are the representations and warranties clauses and their qualifiers. The purpose of this dissertation is to examine the validity of the 'best knowledge' qualifier in representations and warranties in the Brazilian legal system and its effectiveness considering the limits imposed by such system. It seeks, therefore, to analyze the concept of the 'best knowledge' qualifier in its original system, the Common Law, and then bring the discussion to the legal environment of the Brazilian system, enabling the conclusion that the validity of the clause follows the principle of freedom of choice but it is limited to the values brought by the principle of objective good-faith and its related duties. Once verified the validity of the legal institute in the Brazilian legal system, its effectiveness relates to the allocation of responsibility between the parties related to knowledge and the consequences of this allocation.